Further Increase in the Expression of Activation Markers on Monocyte-Derived Dendritic Cells in Coronary Artery Disease Patients with Ectasia Compared to Patients with Coronary Artery Disease Alone. (27th May 2010) - Yildirim, Nesligul; Tekin, Ishak Ozel; Arasli, Mehmet; Aydin, Mustafa
Abstract : Background . Coronary artery ectasia (CAE) is defined as localized or diffuse dilation of the coronary arteries. There are scarce data about the role of dendritic cells in CAE development. In this study we investigated the activation markers on the surface of monocyte-derived dendritic cells (mDCs) in coronary artery disease (CAD) patients with or without CAE. Method . The study consisted of 6 patients who had obstructive CAD with CAE, 6 CAD patients without CAE and 6 subjects with angiographically normal coronary arteries. mDCs were cultivated from peripheral blood monocytes. Surface activation markers were detected by flow cytometry. Results . CAD patients with CAE were detected to have significantly higher mean fluorescence intensities of CD11b, CD11c, CD54, CD83, CD86 and MHC Class II molecules on mDCs in comparison to CAD patients without CAE and normal controls (P < .001 for all). A significant positive correlation was found between the number of vessels with CAE and the levels of CD11c, CD86, and MHC Class II molecules. Conclusion . mDCs display an increased cell surface concentration of activation molecules in CAD patients with CAE compared to patients with CAD alone. DC activation may play an important role for CAE development in patients with CAD.